Tips for transitioning to and from international soccer camps - Oliva-Lozano, J. M.; Norman, D.; Sherlock, N.; Vidal, M.; Webb, J.; Cost, R.; Gabbett, T. J. (Sports Health: A Multidisciplinary Approach, 2025)
Every year, as elite soccer seasons roll on, National Federations face a familiar challenge: managing players through the demanding transitions between club and national team duties. These transitions are more than logistical nightmares; they require careful consideration of recovery, player wellness, and performance, especially when long-distance travel and intense match schedules come into play. Eastward travel, in particular, complicates matters, often leading to poor sleep, jet lag, and reduced performance within the first 72 hours of arrival. Although clubs benefit from continuous player monitoring,10 national teams often have limited time with their players. This lack of regular interaction adds another layer of complexity when preparing for competitions. In this editorial, we aim to offer practical solutions to help clubs and national teams navigate these challenges more effectively, ensuring smoother transitions for players, and reducing the risks of injury and performance issues.